Expansion of broadcasting:: an analysis of the granting policy of the Bolsonaro government - Pieranti, Octavio Penna (2023)
The objective of this article is to analyze the granting policy of the Jair Bolsonaro government (2019-2022), based on a survey, carried out by the author, of the acts related to the 5,072 new stations, published in the editions of the Diário Oficial da União (DOU) in this period. Based on this database, which had a primary source as a reference, it was verified (a) the need for advances in objective criteria for new grants; (b) the preponderance of new stations related to the TV digitization process; (c) the significant increase in grants for the State; and (d) the lack of emphasis given to community and educational broadcasting services.